The effect of isovolemic hemodilution with oxycyte, a perfluorocarbon emulsion, on cerebral blood flow in rats. - Zhong-jin Yang; Chrystal D Price; Gerardo Bosco; Micheal Tucci; Nagwa S El-Badri; Devanand Mangar; Enrico M Camporesi (PLoS ONE, 2008)
BACKGROUND: Cerebral blood flow (CBF) is auto-regulated to meet the brain's metabolic requirements. Oxycyte is a perfluorocarbon emulsion that acts as a highly effective oxygen carrier compared to blood. The aim of this study is to determine the effects of Oxycyte on regional CBF (rCBF), by evaluating the effects of stepwise isovolemic hemodilution with Oxycyte on CBF. METHODOLOGY: Male rats were intubated and ventilated with 100% O(2) under isoflurane anesthesia. The regional (striatum) CBF (rCBF) was measured with a laser doppler flowmeter (LDF). Stepwise isovolemic hemodilution was performed by withdrawing 4ml of blood and substituting the same volume of 5% albumin or 2 ml Oxycyte plus 2 ml albumin at 20-minute intervals until the hematocrit (Hct) values reached 5%. PRINCIPAL FINDINGS: In the albumin-treated group, rCBF progressively increased to approximately twice its baseline level (208+/-30%) when Hct levels were less than 10%. In the Oxycyte-treated group on the other hand, rCBF increased by significantly smaller increments, and this group's mean rCBF was only slightly higher than baseline (118+/-18%) when Hct levels were less than 10%. Similarly, in the albumin-treated group, rCBF started to increase when hemodilution with albumin caused the CaO(2) to decrease below 17.5 ml/dl. Thereafter, the increase in rCBF was accompanied by a nearly proportional decrease in the CaO(2) level. In the Oxycyte-treated group, the increase in rCBF was significantly smaller than in the albumin-treated group when the CaO(2) level dropped below 10 ml/dl (142+/-20% vs. 186+/-26%), and rCBF returned to almost baseline levels (106+/-15) when the CaO(2) level was below 7 ml/dl. CONCLUSIONS/SIGNIFICANCE: Hemodilution with Oxycyte was accompanied with higher CaO(2) and PO(2) than control group treated with albumin alone. This effect may be partially responsible for maintaining relatively constant CBF and not allowing the elevated blood flow that was observed with albumin.